2022
DOI: 10.2147/jir.s347702
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the TCR β Chain Repertoire in Peripheral Blood from Hepatitis B Vaccine Responders and Non-Responders

Abstract: Background: Hepatitis B (HepB) vaccination can effectively prevent the prevalence of hepatitis B virus (HBV) infection. However, the incidence of vaccination failure is about 5~10% and the underlying molecular mechanisms are poorly understood. T cells have an essential role in the recipient's immune response to vaccine, which could be elucidated by high-throughput sequencing (HTS) and bioinformatics analysis. Methods: We conducted HTS of the T cell receptor β chain (TRB) complementarity-determining region 3 (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…Zhan et al identi ed motifs such as "CASSLG" and "GAGPLT" as a consensus sequence potentially linked to anti-HBs antibody production, and motifs like "NYGYTF" and "NSPLHF" as potential HBV-speci c motifs, providing new insights for HBV vaccination and treatment [39] . Furthermore, nearly 80% of "KLNSPL," "GNEQ," and "LLRWYGY" in BV27/J1-6 of TCR CDR3 was found in responders to the hepatitis B vaccine [40] . Our study, for the rst time, revealed that DP and HC groups shared predominant motifs for TCR CDR3 V(D)J combinations, while the RP group exhibits entirely distinct motifs, suggesting that motifs like "VCLCKS" and "CRRRRK" in the RP group may be effective in the anti-HBV response (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhan et al identi ed motifs such as "CASSLG" and "GAGPLT" as a consensus sequence potentially linked to anti-HBs antibody production, and motifs like "NYGYTF" and "NSPLHF" as potential HBV-speci c motifs, providing new insights for HBV vaccination and treatment [39] . Furthermore, nearly 80% of "KLNSPL," "GNEQ," and "LLRWYGY" in BV27/J1-6 of TCR CDR3 was found in responders to the hepatitis B vaccine [40] . Our study, for the rst time, revealed that DP and HC groups shared predominant motifs for TCR CDR3 V(D)J combinations, while the RP group exhibits entirely distinct motifs, suggesting that motifs like "VCLCKS" and "CRRRRK" in the RP group may be effective in the anti-HBV response (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…reported increased frequencies of motifs such as "NTE," "QETQ," and "GG-Q (E)-ETQ" in respondents to the hepatitis B vaccine compared to non-respondents in TRB repertoire analysis [40] . Moreover, we found that "xxxxxW" was speci cally expressed in the IGH V(D)J combinations of the RP group, suggesting its potential as a protective motif against anti-HBV infection (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To elucidate the molecular basis of the 5~10% failure rate of the hepatitis B vaccine, Yang et al. ( 48 ) conducted high-throughput sequencing and bioinformatics analysis of TRB CDR3 repertoires and found that the diversity of TRB CDR3 was significantly increased in responders compared to non-responders, which suggested that individuals with increased TCR diversity had better vaccine responses. Our results showed an increased TCR diversity after vaccination, suggesting that the SARS-CoV-2 inactivated vaccine elicits adaptive T cell immunity that can facilitate the recognition of multiple antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the motif “NYGYTF” and “NSPLHF” could be the HBV-specific motif, and the motif “GAGPLT” may relate to anti-HBs production, which paves the way for HBV vaccination and treatment. Yang et al have reported that the motifs “NTE,” “QETQ,” and “GG-Q (E)-ETQ” were expressed mostly in BV27 and BV7-9, which are significantly increased in hepatitis B vaccine responders compared to those in non-responders in the TRB repertoire analysis of hepatitis B vaccine response [ 34 ]. Furthermore, the motif “KLNSPL” was found in nearly 80% of CDR3s in BV27/J1-6 from hepatitis B vaccine responders.…”
Section: Discussionmentioning
confidence: 99%